Center of Mass Compensation during Gait in Hip Arthroplasty Patients: Comparison between Large Diameter Head Total Hip Arthroplasty and Hip Resurfacing. (18th September 2011) - Bouffard, Vicky; Nantel, Julie; Therrien, Marc; Vendittoli, Pascal-André; Lavigne, Martin; Prince, François
Abstract : Objective . To compare center of mass (COM) compensation in the frontal and sagittal plane during gait in patients with large diameter head total hip arthroplasty (LDH-THA) and hip resurfacing (HR). Design . Observational study. Setting . Outpatient biomechanical laboratory. Participants . Two groups of 12 patients with LDH-THA and HR recruited from a larger randomized study and 11 healthy controls. Interventions . Not applicable. Main Outcome Measures . To compare the distance between the hip prosthetic joint center (HPJC) and the COM. The ratio (R HPJC-COM ) and the variability (CV HPJC-COM ) were compared between groups. Hip flexor, abductor, and adductor muscle strength was also correlated between groups while radiographic measurements were correlated with the outcome measures. Results . In the frontal plane, HR shows less variability than healthy controls at push-off and toe-off andR HPJC-COM is correlated with the muscle strength ratios (FR ABD ) at heel contact, maximal weight acceptance, and mid stance. In the sagittal plane, LDH-THA has a higherR HPJC-COM than healthy controls at push-off, andCV HPJC-COM is significantly correlated withFR FLEX . Conclusions . One year after surgery, both groups of patients, LDH-THA and HR, demonstrate minor compensations at some specific instant of the gait cycle, in both frontal and sagittal planes. However, their locomotion pattern is similar to the healthy controls.